CFD SIMULATION OF THE USE OF AIRFOIL BASED BLADES ON THE PERFORMANCE OF A 2 BLADE SAVONIUS TURBINE - Rendi R (Universitas Muhammadiyah Semarang, 2023)
Wind turbine is one of the alternative power generation equipment that can be developed as a power plant in rural areas which has a potential wind speed of 2-6 m/s. The most ideal type of wind turbine to be operated at slow wind speeds (2-6 m/s) is the Savonius rotor type turbine, but unfortunately this type of turbine has a weakness, namely its relatively low efficiency. The purpose of this research is to study the performance of the turbine with the development of new airfoil-based blades and the characteristics of the fluid pattern around the blades. The method used in this research is to simulate a turbine with ANSYS Fluent R2020. The results showed that the maximum tsr was 0.6 giving the highest Cp 0.14.